In and out: factors influencing two decades of straying and homing by Pacific salmon within the Columbia River basin - Peter A. H. Westley; Andrew H. Dittman; Benjamin W. Nelson; Morgan H. Bond; Molly Payne; Thomas P. Quinn (Royal Society Open Science)
In addition to patch size and spatial isolation, habitat quality can also influence attractiveness of patches to dispersing individuals. Using mark recapture data from 19 populations of Chinook salmon (Oncorhynchus tshawytscha) across 23 years in the Columbia River basin, USA, we estimated rates of emigration and immigration among sites, yielding 358 site-year comparisons of donor and recipient straying, representing over 1.5 million individual tag recoveries. The factors associated with emigration and immigration were quantified with a Bayesian zero-inflated beta regression model. We found lower rates of straying from larger basins than from smaller basins and that donor and recipient straying decreased in years when relatively high numbers of salmon from a given river returned compared with years when fewer returned. Additionally, water temperature was positively associated with both immigration into and emigration out of hatcheries, increasing by approximately 0.5% for every degree of warming, suggesting consequences for both donor and recipient populations. This work suggests that dispersal rates may increase in a warming world, which in turn has implication for the flow of both individuals and, potentially, beneficial or deleterious genes.